Exploring Psilocybe cubensis Strains: Cultivation Techniques, Psychoactive Compounds, Genetics and Research Gaps - Kurzbaum, Eyal; Páleníček, Tomáš; Shrchaton, Amiel; Azerrad, Sara; Dekel, Yaron (Journal of fungi (Basel, Switzerland), 2025)
Psilocybe cubensis, a widely recognized psychoactive mushroom species, has played a significant role in both historical and modern therapeutic practices. This review explores the complex interplay between genetic diversity, strain variability and environmental factors that shape the biosynthesis of key psychoactive compounds, including psilocybin and psilocin. With many strains exhibiting substantial variability in their phenotypic characteristics and biochemical content, understanding and documenting this diversity is crucial for optimizing therapeutic applications. The review also highlights advances in cultivation techniques, such as submerged fermentation of the mycelium, and innovative analytical methodologies that have improved the precision of compound quantification and extraction. Although there is limited scientific information on P. cubensis due to nearly four decades of regulatory restrictions on psychedelic research, recent developments in genetic and biochemical studies are beginning to provide valuable insights into its therapeutic potential. Furthermore, this review emphasizes key knowledge gaps and offers insights into future research directions to advance the cultivation, scientific documentation of strain diversity, regulatory considerations and therapeutic use of P. cubensis.
Keywords: mushroom; genetics; fungi; psilocin; mycelium; psychoactive; psilocybin; Psilocybe